Lipoxin A4 augments host defense in sepsis and reduces Pseudomonas aeruginosa virulence through quorum sensing inhibition. Issue 6 (10th March 2016) - Wu, Benedict; Capilato, Joseph; Pham, Michelle P.; Walker, Jean; Spur, Bernd; Rodriguez, Ana; Perez, Lark J.; Yin, Kingsley
ABSTRACT: Bacterial infections can quickly turn into sepsis, with its attendant clinical sequelae of inflammation, tissue injury, and organ failure. Paradoxically, sustained inflammation in sepsis may lead to immune suppression, because of which the host is unable to clear the existing infection. Use of agents that suppress the inflammatory response may accelerate host immune suppression, whereas use of traditional antibiotics does not significantly affect inflammation. In this study, we investigated whether lipoxin A4 (LXA4 ), a specialized, proresolution lipid mediator, could increase neutrophil phagocytic activity as well as reduce bacterial virulence. Using the mouse cecal ligation and puncture (CLP) model of sepsis, the administration of LXA4 (7 μg/kg i.v.) 1 h after surgery increased neutrophil phagocytic ability and Fcg receptor I (CD64) expression. Ex vivo studies have confirmed that the direct addition of LXA4 to CLP neutrophils increased phagocytic ability but not CD64 expression. LXA4 did not affect neutrophils taken from control mice in which CD64 expression was minimal. Taken together with in vivo data, these results suggest that LXA4 directly augments CD64‐mediated neutrophil phagocytic ability but does not directly increase neutrophil CD64 expression. Bacterial communication and virulence is regulated by quorum sensing inducers. In Pseudomonas aeruginosa, virulence is induced with release of various virulence factors, by N ‐3‐oxododecanolyl homoserine lactone binding to the quorum sensing receptor, LasR. We show that LXA4 is an inhibitor of LasR in P. aeruginosa and that it decreases the release of pyocyanin exotoxin. These results suggest that LXA4 has the novel dual properties of increasing host defense and decreasing pathogen virulence by inhibiting quorum sensing.—Wu, B., Capilato, J., Pham, M. P., Walker, J., Spur, B., Rodriguez, A., Perez, L. J., Yin, K. Lipoxin A4 augments host defense in sepsis and reduces Pseudomonas aeruginosa virulence through quorum sensing inhibition. FASEB J. 30, 2400–2410 (2016). www.fasebj.org